(untitled) (AYUSHDHARA, 2025)
Obstruction in the fallopian tubes is a significant factor that can lead to infertility in females. This condition is pathophysiologically recognized as a Tridoshaja Vyadhi with Vata Dosha being the dominant contributing factor. Tubal constriction, fibrosis, and stenosis are pathophysiological manifestations attributed to the Ruksha (dry) and Khara (coarse) attributes of vitiated Vata Dosha. Kapha Dosha, owing to its obstructive (Avarodhak) nature, plays a role in causing blockages in the fallopian tubes. Pitta Dosha plays a pivotal role in mediating Paka (inflammatory transformation), especially when triggered by pathogenic infections. Ayurveda address this condition by targeting the underlying Dosha imbalances. This case study presents a patient diagnosed with infertility due to tubal blockage who underwent an Ayurvedic treatment regimen. The intervention involved Shaman Chikitsa, which included a combination of Ayurvedic medicines aimed at balancing the vitiated doshas, enhancing digestion and metabolism, and thereby restoring the patency of the fallopian tubes. The patient experienced a successful outcome reflecting changes in her Radiograph HSG, highlighting the potential of Ayurveda in managing tubal blockage and promoting fertility.